Battery with low internal resistance metallized

By using low-thickness electrodes, high porosity electrodes, multi-layer electrode coatings and patterned electrode coatings in lithium-ion batteries, combined with thin metallized current collectors, the problem of high internal resistance of lithium-ion batteries is solved, and the effects of low internal resistance, high safety and high power density are achieved.

CN119542428APending Publication Date: 2025-02-28SOTERIA BATTERY INNOVATION GROUP INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411225624.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-12-31
Filing Date
2020-11-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Due to the high internal resistance of existing lithium-ion batteries, they are prone to thermal runaway and short-circuit problems, resulting in safety hazards and power losses.

Method used

Low-thickness electrodes, high porosity electrodes, multi-layer electrode coatings and patterned electrode coatings are used to combine with thin metallized current collectors to reduce the internal resistance of the battery.

Benefits of technology

The low internal resistance of lithium-ion batteries is achieved, the safety and power density is improved, the risk of thermal runaway is reduced, while maintaining the high energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542428A_ABST
    Figure CN119542428A_ABST
Patent Text Reader

Abstract

A lithium electrochemical energy generation and storage device includes a negative electrode, a positive electrode, at least one separator between the negative electrode and the positive electrode, an electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode; wherein the current collector exhibits an electrical resistivity greater than 0.005 ohm / square; wherein the electrochemical device exhibits a 2C capacity greater than 70% of the capacity measured at 0.5 C, such a current collector further comprising an insulating support layer coated with at least one electrically conductive layer wherein the electrically conductive layer has a thickness of less than 2 microns.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of November 10, 2020, application number 202080006057.6, and invention name “Battery with a metallized film current collector having low internal resistance”. Technical Field

[0002] The present technology relates to improvements in the structural components and physical properties of lithium battery products, thereby providing lower resistance than standard rechargeable battery types (e.g., high-power lithium-ion battery types as an example). This structural modification involves a thinner metal current collector structure that increases the internal resistance level of the battery cell, and is accompanied by a reduction in the internal resistance of the battery cell by modifying the electrode coating as an adjustment in this regard. Utilizing low-thickness electrodes, high-porosity electrodes, higher-conductivity electrode coatings, multilayer electrode coatings with different levels of conductive materials, and pattern coatings with different resistance areas for directional results, all of which work simultaneously with thin metallized current collectors in this regard. The present invention also provides battery products including these improvements and methods of use thereof. The present technology relates to batteries with metallized thin-film current collectors with low internal resistance, which are used to reduce the internal resistance of lithium-ion batteries. Background Art

[0003] Rechargeable power batteries (e.g., not limited to lithium-ion batteries) remain popular as power sources throughout the world and are becoming increasingly important in numerous products. From rechargeable power tools to electric vehicles to ubiquitous cellular phones (such as tablets, handheld computers, etc.), lithium batteries (of different ion types) are used as the primary power source due to their reliability, rechargeability mentioned above, and long service life.

[0004] These problems exist primarily due to manufacturing issues, both in terms of the individual battery components that are made and in terms of how such components themselves are configured into individual batteries. Upon closer inspection, lithium batteries are currently made of six major components: a positive electrode material; a positive electrode current collector (such as aluminum foil) coated with the positive electrode material; a negative electrode material; a negative electrode current collector (such as copper foil) coated with the negative electrode material; a separator located between each negative and positive electrode layer and typically made of a plastic material; and an electrolyte, which acts as a conductive organic solvent that saturates the other materials, thereby providing a mechanism for conducting ions between the negative and positive electrodes. These materials are typically packaged in cans (such as the prior art) Figure 1As shown), they are wound together, or stacked together. There are many other configurations that can be used for such battery production purposes, including soft pack batteries, square batteries, button batteries, cylindrical batteries, wound square batteries, wound soft pack batteries, and the list goes on. These batteries can provide energy for various applications for thousands of charge and discharge cycles without any obvious safety incidents when they are properly made and handled with care. However, as mentioned above, certain events, especially certain defects, can cause internal short circuits between internal conductive materials, resulting in heating and internal thermal runaway, which is known to be the ultimate cause of fires in such lithium batteries. As mentioned above, such events may also be caused by internal defects, including the presence of metal particles in the battery, burrs on the current collector material, fine points or holes in the separator (whether included during subsequent processing or caused during subsequent processing), misalignment of the battery layers (unwanted conductivity caused by leaving "openings"), external debris that penetrates into the battery (such as road debris that hits a moving vehicle), the fragmentation and / or instability of the battery cell itself (for example, due to an accident), charging the battery cell in a confined space, etc. Generally speaking, these types of defects are known to result in the creation of a small electronic conduction path between the negative electrode and the positive electrode. When such an event occurs, if the battery is subsequently charged, such a conduction path may result in the discharge of the battery cell, which ultimately generates excessive heat, thereby damaging the battery structure and endangering the underlying devices powered thereby. Combined with the presence of a flammable organic solvent material as the battery electrolyte (which is generally necessary for the battery to be operable), this excessive heat has been shown to cause it to ignite, ultimately creating a very dangerous situation. Such problems are difficult to control, at least once they begin, and have resulted in serious injuries to consumers. By providing a battery that delivers electrical energy without damaging the flammable organic electrolyte in this manner, this potentially catastrophic situation can certainly be avoided.

[0005] Excessive internal heat generation may further cause the plastic separator to shrink, causing it to move away from the battery, separate, or otherwise increase the short circuit area within the battery. In this case, the larger exposed short circuit area within the battery may result in continued current flow and increased heat therein, leading to a high temperature event, which may cause significant damage to the battery cell, including rupture, venting, and even flames and fire. Such damage is particularly problematic because the possibility of fire and worse consequences can occur quickly, and may cause the battery and potentially the underlying device to explode, thereby also posing a significant risk to the user.

[0006] Lithium batteries (of various types) are particularly susceptible to problems associated with short circuits. As described above, typical batteries tend to exhibit increased discharge rates when exposed to high temperatures, which can sometimes lead to uncontrolled (runaway) combustion and fire as described above. Due to these possibilities, certain regulations have come into effect to govern the actual use, storage, and even transportation of such battery items. Of course, the ability to implement appropriate protocols to prevent runaway events associated with short circuits is very important. However, there remains the question of how to actually address such issues, especially when parts production is provided from countless suppliers and many different locations around the world.

[0007] Some previous disclosures have mentioned the use of metallized films as current collector structures in lithium-ion batteries, including Japanese Patent Application No. 11410796. Such disclosures, as well as others made more recently, are very limited in providing the internal resistance within the target power battery itself, without any other structural modifications as an adaptation thereto. For example, CATL has recently taught the use of current collector films (metallization) for safety purposes; however, as described above, such use is limited to the effect of very thin metal coatings that require high internal resistance. Therefore, the present CATL disclosure is limited to defining the required level of internal resistance R of the battery related to the battery capacity CAP as the product of R×CAP is above a specific parameter, which is 40 in this case. However, in the present invention, and in all cases involving the "capacity" of the battery, such measurements are made at a rate of 0.2C or less. Such a high internal resistance can contribute to the good safety performance of lithium-ion batteries because such an internal resistance level can reduce the current when there is an internal short circuit or a short circuit caused by damage. Of course, the higher the internal resistance, the lower the current, which reduces the rate at which heat is generated due to the short circuit, thereby reducing the possibility of the battery being driven into thermal runaway. Thus, it has now been recognized that such metallized thin film current collectors can be used in conjunction with power generation cells while exhibiting low internal resistance, which is quite novel and contrary to this particular CATL teaching (achieving high safety associated with using ultra-thin metal coatings on metallized films with high resistance results).

[0008] Therefore, it is generally believed that such reduced metal content (e.g., from bulk to metallized film) necessarily contributes to increasing the internal resistance of the target power cell, thereby improving its safety. Therefore, the standard involving such metallized film utilization within lithium-ion cells, etc., is that the only way to achieve such safety levels (e.g., to prevent thermal runaway) is to provide a cell with a high internal resistance, and that such high resistance levels are the source of the increased safety in this regard.

[0009] However, it has been found that low internal resistance batteries are necessary to deliver or receive high power, essentially allowing for improved safety, but at the same time giving the power levels required for the viability of such rechargeable batteries in the industry. For example, when it comes to electric vehicles, there have indeed been some incidents that have shown problems related to thermal runaway due to short circuits caused by the manufacture and / or damage to the rechargeable battery itself. With the use of high internal resistance metallized thin film current collectors, the tendency for such thermal runaway to occur is reduced, but power loss, thereby reducing the effectiveness and / or duration of effectiveness of recharging the rechargeable battery, whereby high-level activation and utilization are essentially impaired. In other words, to achieve efficient and fast charging in such electric vehicles, high power reception is essentially required. Similarly, it is difficult to achieve the feasibility and safety of utilization with the sole goal of providing high internal resistance in such high-power battery applications. Hybrid electric vehicles also require extremely fast charging capabilities, and therefore require similar high power charging levels (while also requiring improved safety). In this regard, electric aircraft such as drones, air taxis, etc. require very high power levels to take off and land, at least for safety reasons. The same problem arises as it relates to the ability to quickly charge batteries in mobile phones, laptops and other devices, and of course to the safety issues that may arise from short circuits and thermal runaway. In other words, the required safety needs to be achieved through thinner metal current collector structures, but the latest technology in this regard has overcompensated in the sense that power levels have been compromised to such an extent that such limited thin-film current collector considerations cannot be a solution within the rechargeable power battery industry.

[0010] Additionally, the ability to reduce the weight of the initial current collector structure will certainly help in some ways by reducing the overall weight of the target battery. Nonetheless, this limited modification does not allow for high power enhancements because such structural modifications would create high internal resistance in the target battery without further compensating for the lack of power generation. It would be an unexpected improvement to further enhance the ability to produce energy as the weight is reduced. However, so far, as described above, the only weight reduction for such power batteries has been related to safety only through the increase in high internal resistance. The present invention provides such a highly desirable solution that makes lithium batteries very safe, reliable and suitable for high-power devices in multiple markets.

[0011] Therefore, there is a need for a new and improved battery having a metallized thin film current collector with low internal resistance that can be used to reduce the internal resistance in a lithium ion battery. In this regard, the present technology substantially meets this need. In this regard, the low internal resistance battery with a metallized thin film current collector according to the present technology substantially departs from the conventional concepts and designs of the prior art, and does so to provide a device that is primarily developed for reducing the internal resistance in a lithium ion battery. Summary of the invention

[0012] In view of the above-mentioned disadvantages inherent in energy storage devices of the type known in the prior art, the present technology provides an improved battery with a metallized thin film current collector with low internal resistance, and overcomes the above-mentioned disadvantages and shortcomings of the prior art. Therefore, the general purpose of the present technology (which will be described in more detail later) is to provide a new and improved battery and method with a metallized thin film current collector with low internal resistance, which has all the advantages of the above-mentioned prior art and many new features, which lead to a battery with a metallized thin film current collector with low internal resistance, which cannot be expected, presented as obvious, taught, or suggested by the prior art (whether alone or in any combination thereof).

[0013] According to one aspect, the present technology may include a lithium electrochemical energy generation and storage device, the device including a negative electrode, a positive electrode, at least one separator between the negative electrode and the positive electrode, an electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode. The current collector exhibits a resistivity greater than 0.005 ohms / square. The electrochemical device exhibits a 2C capacity greater than 70% of the capacity measured at 0.5C. The current collector also includes an insulating support layer coated with at least one conductive layer having a thickness of less than 2 microns.

[0014] According to another aspect, the present technology may include a lithium electrochemical energy generation and storage device comprising a negative electrode, a positive electrode, at least one separator between the negative electrode and the positive electrode, an electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode. The current collector may exhibit a resistivity greater than 0.005 ohms / square. At least one of the negative electrode or the positive electrode is configured to achieve low resistivity by including at least one of the following items: a) an electrode having a thickness of less than 70 microns; b) an electrode coating containing more than 6% by weight of a conductive additive; c) an electrode coating showing a porosity greater than 35%; d) an electrode coating having multiple layers; and e) an electrode coating showing a dispersed pattern of coating materials. At least one component of the pattern includes a high energy, low conductivity region, and at least one other component of the pattern includes a higher conductivity region. The conductivity can be obtained by the presence of a high conductive material content or a high porosity material.

[0015] According to another aspect, the present technology may include an energy storage device including a negative electrode and a positive electrode, a first separator interposed between the negative electrode and the positive electrode; an electrolyte; a first current collector in contact with at least one of the negative electrode and the positive electrode; a second current collector in contact with at least one of the negative electrode and the positive electrode, at least one electrode of the second current collector being opposite to at least one electrode of the first current collector; and a second separator in contact with the second current collector. At least one of the first current collector and the second current collector exhibits a resistivity greater than 0.005 ohms / square.

[0016] In some or all embodiments, the device may exhibit a resistance of less than 15 milliohms.

[0017] In some or all embodiments, the device may exhibit less than 4.0 mAh / cm 2 The energy density of the electrode area.

[0018] In some or all embodiments, the device may exhibit a product of a capacity CAP and a resistance R, wherein CAP×R is less than 40 mOhm-Ah.

[0019] Some or all embodiments may further include a tab connected to the first current collector and configured to contact an external contact.

[0020] In some or all embodiments, the first current collector and the second current collector each include a metal film coated thereon.

[0021] In some or all embodiments, the metal film of the first current collector and the metal film of the second current collector are different metals.

[0022] In some or all embodiments, the metal film of at least one of the first current collector and the second current collector may have a coating thickness of less than 5 microns in total.

[0023] In some or all embodiments, the negative electrode and the positive electrode may be porous, exhibiting a porosity of at least 35%.

[0024] In some or all embodiments, the negative electrode and the positive electrode may each include an electrode coating comprising greater than 6 wt % of a conductive additive.

[0025] In some or all embodiments, the negative electrode and the positive electrode may each have multiple layers including a top layer having a higher conductivity than each successive lower layer.

[0026] In some or all embodiments, the negative electrode and the positive electrode may each have multiple layers including a top layer that exhibits a higher porosity than each successive underlying layer.

[0027] In some or all embodiments, the positive electrode is a patterned electrode, wherein a portion of the positive electrode includes a first region interspersed with a second region, wherein the first region has a first energy or a first conductivity property, and the second region has a second energy or a second conductivity property greater than the first region, thereby producing a conductivity gradient.

[0028] According to another aspect, the present technology may include an electrochemical energy generation and storage device (power cell, rechargeable battery, etc.), comprising a negative electrode, a positive electrode, at least one separator between the negative electrode and the positive electrode, an electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode. The current collector exhibits a resistivity greater than 0.005 ohms / square (preferably greater than 0.01, more preferably greater than 0.015, most preferably at least 0.025 ohms / square). The device exhibits a capacity CAP and a resistance R such that the product CAP×R is less than 40mOhm-Ah (preferably less than 35, more preferably less than 30, more preferably less than 25, most preferably less than 20mOhm-Ah). The electrochemical device exhibits a 2C capacity greater than 70% of the capacity measured at 0.2C (where 2C represents a 30 minute discharge and 0.2C represents a 5 hour discharge) (preferably greater than 75%, more preferably greater than 80%, still more preferably greater than 85%, most preferably greater than 90%).

[0029] In some or all embodiments, the device may exhibit a resistance of less than 15 milliohms (preferably less than 12, more preferably less than 10, more preferably less than 8, even more preferably less than 6, and most preferably less than 4 milliohms). Of course, larger batteries naturally exhibit lower internal resistance, so it is desirable to obtain batteries with high capacity and low internal resistance. Therefore, the battery can have both a low resistance target and a capacity target, with the higher resistance allowing a lower capacity limit. The capacity can be limited to less than 5Ah, preferably less than 20Ah, more preferably less than 40Ah, even more preferably less than 100Ah, and most preferably less than 200Ah. Such examples can include batteries with limited capacity below 10Ah and resistance below 10mOhms.

[0030] In some or all embodiments, the device may exhibit less than 4.0 mAh / cm 2 (Preferably less than 3.5 mAh / cm 2 , more preferably less than 3.0 mAh / cm 2 , more preferably less than 2.5 mAh / cm 2 , even more preferably less than 2.0 mAh / cm 2 , more preferably less than 1.5, most preferably less than 1.0 mAh / cm 2) electrode area energy density. In such a unique device, the current collector exhibits a certain increased resistance, while the entire device exhibits a certain reduced resistance, or alternatively, the capacitance and / or electrode area energy density meet certain constraints that have not been previously imposed. This difference between the increased resistance of the current collector and the different physical properties of the device related to the electrode structure provides this novel measurement data, which simultaneously provides higher power (for charging and discharging) for the entire device with high resistance (low thickness and weight of the current collector).

[0031] On the other hand, the technology of the present invention can provide a non-conductive current collector component for an electrode structure, wherein the non-conductive current collector component is a polymer film or fabric having a metal layer on each of its top and bottom surfaces, wherein the negative electrode and / or the positive electrode (as an electrode, one of which is in contact with the current collector) is provided with one or more of the following physical structures: a) a porous electrode showing a porosity of at least 35% (more preferably at least 40%, more preferably at least 45%, even more preferably at least 50%, most preferably at least 55%); b) an electrode coating, wherein such a coating contains a higher loading or higher conductivity additive in the electrode material, wherein the conductive additive can be graphite, carbon, etc., and is in a large amount. c) a multilayer electrode wherein the top layer has a higher conductivity (or carbon content) than each successive lower layer; d) a multilayer electrode wherein the top layer exhibits a higher porosity than each successive lower layer; and e) a patterned electrode wherein a portion of the electrode consists of high energy (low conductivity) regions interspersed with higher conductivity regions, wherein the conductivity gradient is achieved by different conductive material content levels or material types, or by different porosity measurements (wherein a higher and lower gradient exists).

[0032] In some or all embodiments, the patterned coating can be laid down by various well-known printing techniques that allow patterns of different materials to be obtained. Such multilayer structures can be produced by multiple passes, depositing one layer per pass, or by coextrusion of multiple material layers through a single orifice or print head.

[0033] According to another aspect, the present technology can provide an initial metallized thin film current collector that greatly limits the transmission time of the current level applied to the target current collector surface through the probe tip (so as to controllably simulate internal manufacturing defects, dendrites, or external events that cause internal short circuits within the target battery) to less than 1 second, preferably less than 0.01 seconds, more preferably less than 1 millisecond, and most preferably, perhaps even less than 100 microseconds, especially for larger currents.

[0034] In some or all embodiments, the current will be limited to an internal voltage of the battery of 5.0V, 4.5V, 4.2V or lower, such as 4.0V or 3.8V, but with a minimum of 2.0V.

[0035] In some or all embodiments, a metallized film current collector may be provided having a total thickness (entire metallized polymer substrate) of less than 20 microns, preferably less than 15 microns, more preferably less than 10 microns, even more preferably less than 8 microns, still more preferably less than 6 microns, and most preferably less than 4 microns, with all resistivity measurements being greater than 0.005 ohms / square (preferably greater than 0.01 ohms / square, more preferably greater than 0.015 ohms / square, and most preferably at least 0.025 ohms / square).

[0036] In some or all embodiments, the thin components can be configured to allow a short circuit to react with the metal coating and relative to the overall resistance level to produce a localized area of ​​metal oxide that immediately blocks the current from moving further therethrough, producing excessive temperatures due to the current spike during such a short circuit. However, due to the physical consequences of the thin structure, the resistance level still remains high.

[0037] Some or all embodiments may include temperature-dependent metal (or metallization) materials that shrink due to heat sources during a short circuit or are susceptible to degradation to non-conductive materials at specific material locations (e.g., aluminum oxide degraded from an aluminum current collector, as an example) (as mentioned above in various ways).

[0038] In some or all embodiments, the current collector can be configured to become thermally weak, in stark contrast to the aluminum and copper current collectors used today, which are very thermally stable to high temperatures. As a result, alloys of metals with lower intrinsic melting temperatures can degrade at lower short-circuit current densities, thereby improving the safety advantages of the lithium-based energy devices disclosed herein.

[0039] In some or all embodiments, the battery capacity may be limited to less than 10 Ah and the resistance to less than 10 milliohms.

[0040] In some or all embodiments, the current collector may include a layer of conductive material, such as copper or aluminum, coated on fibers or films that exhibit relatively high shrinkage at relatively low temperatures.

[0041] In some or all embodiments, the current collector may include a thermoplastic film having a melting temperature below 250° C., or even 200° C., and may include polyethylene terephthalate, nylon, polyethylene, or polypropylene as non-limiting examples.

[0042] In some or all embodiments, the current collector may include a layer of conductive material, such as copper or aluminum, coated on a fiber or film, which, as described above, can expand or dissolve in the electrolyte when the material is heated to a temperature relatively high compared to the operating temperature of the battery but low compared to temperatures that may cause thermal runaway.

[0043] In some or all embodiments, the polymer configured to swell in a lithium-ion electrolyte may be polyvinylidene fluoride or polyacrylonitrile.

[0044] In some or all embodiments, the internal electrical fuse generation process can coat a substrate with a metal (e.g., aluminum) that is configured to oxidize under heating, with a total metal thickness much lower than that typically used for lithium batteries. The thin aluminum current collector can include a coating having a total thickness of less than 5 microns, less than 2 microns, less than 1 micron, or less than 700nm or 500nm. The coating can include a sufficient amount or thickness of metal to provide sufficient conductivity to energize the battery. The thickness can be greater than 10nm, preferably greater than 50nm, or even greater than 100nm, or greater than 200nm.

[0045] In some or all embodiments, the areal density may be less than 30 g / m2, preferably less than 25 g / m2, more preferably less than 20 g / m2, and most preferably less than 15 g / m2.

[0046] In some or all embodiments, the breaking of the conductive path can be achieved by providing a current collector with limited conductivity that will degrade at high current densities around the short circuit, similar to the degradation found in commercial fuses today. This can be achieved by providing a thin film metallized film current collector with a resistivity greater than 5 milliohms / square, or 10 milliohms / square, or potentially preferably greater than 20 milliohms / square, or potentially preferably greater than 50 milliohms / square.

[0047] In some or all embodiments, breaking of the conductive path may be achieved by providing a current collector that will oxidize to a non-conductive material at a temperature lower than that of aluminum, thereby rendering the current collector inert in the short circuit region before the separator degrades.

[0048] In some or all embodiments, the metal in the thin current collector layer capacitor can be any metal that exhibits electrical conductivity, including but not limited to gold, silver, vanadium, rubidium, iridium, indium, platinum, and other metals (essentially, by having very thin current collector layers, the costs associated with the use of such metals can be greatly reduced without sacrificing conductivity, but still allowing for protection against thermal runaway potentials during short circuits or similar events). Likewise, layers of different metals can be used, or even discrete metal regions deposited either internally or as separate layer components can be used.

[0049] In some or all embodiments, one side of a coated current collector substrate may include a different metal species than the opposing side, and may also have a different layer thickness than the other side.

[0050] In some or all embodiments, the interface with the metal of the metallized substrate that allows high current flow can be achieved by face-to-face contact, thereby providing a high surface area between the device that makes electrical contact through the housing and the metallized substrate. This surface area can be higher than 1 square millimeter (10 -12 square meters), or higher than 3 square millimeters, or even higher than 5 square millimeters or more preferably higher than 10 square millimeters.

[0051] When the following detailed description of currently preferred but still illustrative embodiments of the present technology is read in conjunction with the accompanying drawings, many objects, features and advantages of the present technology will be apparent to those of ordinary skill in the art. In this regard, before describing in detail the current embodiments of the technology, it should be understood that the present technology is not limited in its application to the construction details and the arrangement of components set forth in the following description or shown in the accompanying drawings. The present technology can be implemented and realized in various ways. In addition, it should be understood that the phrases and terms used in the present invention are for descriptive purposes and should not be considered restrictive.

[0052] Therefore, those skilled in the art will appreciate that the concepts upon which the present invention is based can be readily used as a basis for designing other structures, methods and systems to achieve the several purposes of the present invention. It is therefore important that the claims be deemed to include such equivalent constructions as long as they do not depart from the spirit and scope of the present invention.

[0053] Another object of the present technology is to provide a new and improved battery with a metallized thin film current collector which has low internal resistance and is easy to manufacture and sell efficiently.

[0054] Another object of the present technology is to provide a new and improved battery with a metallized thin film current collector which has a low internal resistance and has a low manufacturing cost in terms of materials and labor, and is therefore easy to sell to consumers at a low price, thereby making such a battery with a metallized thin film current collector with a low internal resistance economically available to purchasers.

[0055] Another object of the present technology is to provide a novel battery having a metallized thin film current collector with low internal resistance which provides some advantages over the prior art devices and methods while overcoming some of the disadvantages typically associated therewith.

[0056] These and other objects of the present technology, as well as the various novel features of the present technology, are particularly pointed out in the claims annexed to and forming a part hereof. For a better understanding of the present technology, its operating advantages and specific objects attained by its uses, reference should be made to the accompanying drawings and description in which embodiments of the present technology are illustrated. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] The present invention will be better understood and other objects besides the above mentioned objects will become apparent when considering the following detailed description of the present invention. Such description refers to the accompanying drawings, in which:

[0058] Figure 1 It is a prior art schematic diagram of the structure of a wound battery (such as a 18650 battery).

[0059] Figure 2 is a prior art diagram of a side perspective view of a thick coating electrode on a metallized thin film current collector.

[0060] Figure 3 1 is a side perspective view of a thin coating electrode applied to a metallized thin film current collector disclosed in the present invention.

[0061] Figure 4 Yes Figure 3 Top cross-sectional view of a jelly-roll lithium-ion rechargeable battery with electrodes / metallized thin-film current collectors.

[0062] Figure 5 is a prior art diagram of a side perspective view of an electrode using a low porosity coating on a metallized thin film current collector.

[0063] Figure 6 1 is a side perspective view of a high porosity coated electrode applied to a metallized thin film current collector disclosed in the present invention.

[0064] Figure 7 Yes Figure 6 Top cross-sectional view of a jelly-roll type lithium-ion rechargeable battery with a high-porosity electrode / metallized thin-film current collector.

[0065] Figure 8 1 is a side perspective view of a multilayer electrode applied to a metallized thin film current collector disclosed in the present invention.

[0066] Fig. 9 Yes Figure 8 Top cross-sectional view of a jelly-roll type lithium-ion rechargeable battery with a multilayer electrode / metallized film current collector.

[0067] Fig.10 is a side perspective view of a patterned coating electrode applied to a metallized thin film current collector disclosed in the present invention.

[0068] Fig.11 Yes Fig.10 Top cross-sectional view of a jelly-roll type lithium-ion rechargeable battery with patterned electrodes / metallized thin film current collectors.

[0069] In the various drawings, the same reference numerals denote the same parts. DETAILED DESCRIPTION

[0070] A significant advantage of the present invention is the ability to provide a mechanism through structural components to sever the conduction path when an internal short circuit occurs, thereby stopping or significantly reducing the flow of current that could generate heat within the target battery cell.

[0071] Another advantage is the ability to provide such a protective structural form within a lithium battery cell, which also provides beneficial weight and cost improvements for overall battery manufacturing, transportation and utilization. Therefore, another advantage is the creation and maintenance of an internal fuse structure within a target battery cell until it is needed to activate it. Another advantage is the provision of a low internal resistance high power battery with a high resistance thin metal current collector for rapid charge and discharge capabilities. Yet another advantage is the ability to utilize flammable organic electrolyte materials within the battery without any significant tendency to ignite during a short circuit or similar event.

[0072] Therefore, the present invention discloses an electrochemical energy generation and storage device (power battery, rechargeable battery, etc.), which includes a negative electrode, a positive electrode, at least one separator between the negative electrode and the positive electrode, an electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode; wherein the current collector exhibits a resistivity greater than 0.005 ohm / square (preferably greater than 0.01 ohm / square, more preferably greater than 0.015 ohm / square, and most preferably at least 0.025 ohm / square); wherein the device exhibits a capacity CAP and a resistance R, so that the product CAP×R is less than 40mOhm-Ah (preferably less than 35, more preferably less than 30, more preferably less than 25, and most preferably less than 20mOhm-Ah); wherein the electrochemical device exhibits a 2C capacity greater than 70% of the capacity measured at 0.2C (wherein 2C represents 30 minutes of discharge and 0.2C represents 5 hours of discharge) (preferably greater than 75%, more preferably greater than 80%, more preferably greater than 85%, and most preferably greater than 90%). Alternatively, such a device may exhibit a resistance of less than 15 milliohms (preferably less than 12 milliohms, more preferably less than 10 milliohms, more preferably less than 8 milliohms, even more preferably less than 6, and most preferably less than 4 milliohms). Of course, larger batteries will naturally exhibit lower internal resistance, so it is desirable to obtain batteries with high capacity and low internal resistance. Therefore, the battery can have both a low resistance target and a capacity target, with a higher resistance allowing a lower capacity limit. The capacity can be limited to less than 5Ah, preferably less than 20Ah, more preferably less than 40Ah, even more preferably less than 100Ah, and most preferably less than 200Ah. Such examples may include batteries with a capacity limit of less than 10Ah and a resistance of less than 10 milliohms. Alternatively, such a device may also exhibit a capacity of less than 4.0mAh / cm 2 (Preferably less than 3.5 mAh / cm 2 , more preferably less than 3.0 mAh / cm 2 , more preferably less than 2.5 mAh / cm 2 , even more preferably less than 2.0 mAh / cm 2 , more preferably less than 1.5 mAh / cm 2 and most preferably less than 1.0 mAh / cm 2 ) electrode area energy density. In this unique device, the current collector exhibits a certain increased resistance, while the entire device exhibits a certain reduced resistance, or, alternatively, the capacity and / or electrode area energy density meet certain constraints that have not been previously imposed. This difference between the increased resistance of the current collector and the different physical properties of the device related to the electrode structure provides this novel measurement, which simultaneously provides higher power (for charging and discharging) for the entire device with high resistance (low thickness and weight of the current collector).

[0073] With respect to such electrochemical power generation and storage devices, further consideration and unexpected discovery is the ability to provide an electrode structure with a non-conductive current collector component such as a polymer film or fabric (with a metal layer on each of its upper and lower surfaces), wherein the negative electrode and / or the positive electrode (as the electrode in contact with the current collector) is provided with one or more of the following physical structures: a) a porous electrode having a porosity of at least 35% (more preferably at least 40%, more preferably at least 45%, even more preferably at least 50%, most preferably at least 55%); b) an electrode coating, wherein such a coating comprises a higher loading or higher conductivity additive in the electrode material, wherein the conductive additive can be graphite, carbon, etc., and its loading is greater than 6 wt% ( Preferably greater than 8 wt%, more preferably greater than 10 wt%, most preferably greater than 12 wt%), and / or wherein the highly conductive material may also include metal particles and / or high aspect ratio conductive materials (e.g., nanotubes and / or carbon nanofibers); c) a multilayer electrode wherein the top layer has a higher conductivity (or carbon content) than each successive lower layer; d) a multilayer electrode wherein the top layer exhibits a higher porosity than each successive lower layer; and e) a patterned electrode wherein a portion of the electrode consists of high energy (low conductivity) regions interspersed with higher conductivity regions, wherein such conductivity gradient is achieved by different conductive material content levels or material types or by making the porosity measurements different, wherein there are higher and lower gradients. As is known in the art, such patterned coatings can be laid down by various printing techniques that allow patterns of different materials to be achieved. Such a multilayer structure can be produced by multiple passes, depositing one layer per pass, or by coextrusion of multiple material layers through a single hole or print head.

[0074] Therefore, another significant advantage of the present invention is to provide an initial metallized thin film current collector that greatly limits the transmission time of the current level applied to the target current collector surface through the probe tip (so as to controllably simulate the effects of internal manufacturing defects, dendrites, or external events that cause internal short circuits in the target battery) to less than 1 second, preferably less than 0.01 seconds, more preferably less than 1 millisecond, and most preferably, perhaps even less than 100 microseconds, especially for larger currents. Of course, such current will be limited to the internal voltage of the battery, which may be 5.0V, or 4.5V, or 4.2V or even lower, for example, 4.0V or 3.8V, but the minimum value is 2.0V.

[0075] Such a metallized thin film current collector can be provided, and its total thickness (entire metallized polymer substrate) is less than 20 microns, and may be preferably less than 15 microns, and may be more preferably less than 10 microns, and may be even more preferably less than 8 microns, and may still be more preferably less than 6 microns, and may be most preferably less than 4 microns, and all resistivity measurements are greater than 0.005 ohms / square (preferably greater than 0.01 ohms / square, more preferably greater than 0.015 ohms / square, and most preferably at least 0.025 ohms / square). Typical current collectors can exhibit these characteristics, but their weight is much higher than that of current collectors made with reinforced polymer substrates, and there is no inherent safety advantage of this variant disclosed in the present invention. For example, a 10 micron thick copper foil can weigh 90 grams / square meter. However, the weight of the copper-plated foil can be as low as 50 grams / square meter, even as low as 30 grams / square meter, and even less than 20 grams / square meter, all while providing the appropriate electrical properties required for the normal operation of the battery (although the device itself has a high internal resistance). However, in this alternative structure, the very thin components also allow short circuits to react with the metal coating and create local areas of metal oxide that can immediately prevent the current from moving further therethrough relative to the overall resistance level, generating excessive temperatures due to the current spike during such short circuits. However, due to the physical consequences of the thin structure, the resistance level still remains high.

[0076] Another possible option for such a high resistance current collector is to provide a temperature-dependent metal (or metallized) material that shrinks due to a heat source in a short period of time, or easily degrades to a non-conductive material (e.g., alumina degraded by an aluminum current collector, as an example) at a specific material location (as mentioned above in a different manner). In this way, the current collector becomes thermally weak, which is in sharp contrast to the aluminum and copper current collectors used today, which are very stable at high temperatures. As a result, alloys of metals with lower intrinsic melting temperatures can be degraded at lower short-circuit current densities, thereby improving the safety advantages of the lithium-based energy devices disclosed in the present invention. Another option is to make a current collector by coating a layer of conductive material (e.g., copper or aluminum) on a fiber or film that exhibits a relatively high shrinkage rate at a relatively low temperature. These examples include thermoplastic films with a melting temperature below 250°C or even 200°C, which can include polyethylene terephthalate, nylon, polyethylene or polypropylene as non-limiting examples. Another possible way to achieve this result is to make a current collector by coating a layer of conductive material (e.g., copper or aluminum) on a fiber or film as described above, which expands or dissolves in the electrolyte when the material is heated to a relatively high temperature compared to the battery operating temperature but lower than the temperature that may cause thermal runaway. Examples of such polymers that can expand in lithium-ion electrolytes include polyvinylidene fluoride and polyacrylonitrile, but there are other polymers known to those skilled in the art. Another way to achieve this alternative internal electrical fuse generation process is to coat a metal such as aluminum on a substrate that oxidizes when heated, and its total metal thickness is much lower than the metal thickness typically used in lithium batteries. For example, a very thin aluminum current collector used today can be 20 microns thick. A coating with a total thickness of less than 5 microns will interrupt the circuit more quickly, while a coating less than 2 microns, or even less than 1 micron, or even less than 700 nanometers, or less than 500 nanometers will interrupt the circuit more quickly. This coating must also have enough metal to provide enough conductivity to excite the battery, so its thickness should be greater than 10nm, preferably greater than 50nm, even greater than 100nm, or most preferably greater than 200nm. When the use of such a thin conductive coating is combined with a low thickness polymer substrate, it will result in an extremely low current collector area density. Therefore, the area density can be less than 30 grams / square meter, preferably less than 25 grams / square meter, more preferably less than 20 grams / square meter, and most preferably less than 20 grams / square meter. Even so, another method to achieve the interruption of the conductive path is to provide a current collector with limited conductivity, which will degrade under high current densities around the short circuit, which is similar to the degradation found in commercial fuses today. This can be achieved by providing a thin metallized film current collector with a resistivity greater than 5 milliohms / square, or 10 milliohms / square, or potentially preferably greater than 20 milliohms / square, or potentially preferably greater than 50 milliohms / square.As discussed above, this resistance also creates a high internal resistance that can, without any compensation, compromise the power generation and delivery capabilities of the target cell. To overcome this high resistance challenge, past improvements have simply changed the resistance of the current collector. These involve thickness and materials and do not take into account any changes to the electrode type, thickness, material, or for that matter, different resistivities may be further selected for cells designed for high power, which may use relatively low resistances; and / or may use relatively high resistances compared to cells designed for low power and high energy. Another way to achieve interruption of the conductive path is to provide a current collector that will oxidize to a non-conductive material at temperatures much lower than aluminum, thereby rendering the collector inert in the short-circuit area before the separator degrades. Certain aluminum alloys oxidize faster than aluminum itself, and these alloys will cause the conductive path to degrade faster or at lower temperatures. As a possible alternative, any type of metal having such a thin collector layer capacity and exhibiting conductivity may be used, including but not limited to gold, silver, vanadium, rubidium, iridium, indium, platinum and others (basically, with a very thin collector layer, the costs associated with the use of such metals can be greatly reduced without sacrificing conductivity, but still allowing thermal runaway potential to be prevented during a short circuit or similar event). Likewise, layers of different metals may be used, or even discrete metal regions deposited internally or as separate layer components may be used. Of course, likewise, one side of such a coated collector substrate may include different metal substances from the opposite side, and may also have different layer thicknesses in comparison.

[0077] In any case, the ability to utilize metallized thin film current collectors (as opposed to thick metal structures) helps reduce the potential for thermal runaway in rechargeable batteries (e.g., as disclosed in co-applied U.S. Patent Application No. 15 / 700,077, the entire contents of which are incorporated herein by reference). However, again, as previously described, such thin structures produce high resistance levels for the target electrochemical cell (battery, etc.), which compromises the ability of the device to provide high power, fast charging, and fast discharge as required in certain end-use applications. Therefore, it is desirable to provide a method for reducing the overall resistance of the device itself, particularly when liquid electrolyte batteries are involved. The present invention is directed to such improvements in this regard. Standard electrochemical cells include a current collector structure, a separator, and electrodes (negative and positive) for generating charge. The use of metallized thin films as current collectors is limited to standard structures with typical electrode structures and separators (note the Japanese reference cited above). These typical electrodes are metal layers with significant thickness to provide overall stability of the battery (device) and allow for high resistance levels inside. However, in contrast to these standard batteries (electrochemical devices), it has been unexpectedly discovered that certain unexplored electrode material coatings are used on metallized thin film current collectors. Therefore, now presents a different way to provide such thin current collectors for safety (and high resistance levels) with such material coatings on such current collectors to provide effective resistance reducing structures for rapid power generation and so rapid movement to external devices.

[0078] To this end, as described above, it was discovered that the materials associated with such unexpected and counterintuitive use of resistance-reducing electrodes rely on coatings applied to metallized current collector films, including those having specific thicknesses, high porosity levels, high conductivity levels, multilayer structures with conductivity gradients, and patterned coatings with regions of different conductivity gradients. In each instance, this new approach not only provides a lower internal resistance of the target electrochemical cell, but also provides the potential to significantly reduce the weight of such structures (in this regard, as well as in conjunction with the current collector film), thereby not only compensating for the resistance increase associated with the thin current collector metallized film, but also providing an attractive weight reduction for the entire battery (device).

[0079] These advantages allow for low weight, high safety levels, and high power generation (charging and discharging) of rechargeable electrochemical cells (as non-limiting examples, lithium-ion batteries, etc.), which have not been available in the relevant industry to date. In any of the alternative configurations discussed herein, such metallized thin film current collectors ostensibly act as internal fuses within the target energy storage device (e.g., lithium battery, capacitor, etc.). In each case (optional), the electrode coating applied thereto enhances the overall thin structure to a level that provides sufficient strength for structural stability within the target battery (device), but at the same time has the ability to reduce the internal resistance of the overall battery relative to the resistance of the increased metallized thin film current. Therefore, the ability to simultaneously provide safety measures associated with short circuits and potential thermal runaway events and produce significant high power generation results meets a need that has not been explored to date.

[0080] These methods and structures are discussed in more detail below.

[0081] The ion storage material may be, for example, a positive electrode or negative electrode material of a lithium ion battery, which is well known in the art. The positive electrode material may include lithium cobalt oxide LiCoO2, lithium iron phosphate LiFePO4, lithium manganese oxide LiMn2O4, lithium nickel manganese cobalt oxide LiNi x Mn y Co z O2, LiNi x CoAl z O2 or a mixture of the above or other materials known in the art. The negative electrode material may include graphite, lithium titanate Li4Ti5O 12 , hard carbon, tin, silicon or mixtures thereof or other materials known in the art. In addition, the ion storage material may include materials used in other energy storage devices (e.g., supercapacitors). In such supercapacitors, the ion storage material will include activated carbon, activated carbon fibers, carbide-derived carbon, carbon aerogels, graphite, graphene, graphene and carbon nanotubes.

[0082] The coating process can be any coating process known in the art. Knife roll and slot die are common coating processes for lithium ion batteries, but other processes, including chemical plating, can also be used. In the coating process, the ion storage material is usually mixed with other materials, including binders such as polyvinylidene fluoride or carboxymethyl cellulose or other film-forming polymers. Other additives to the mixture include carbon black and other conductive additives.

[0083] The means of connection to the metallized substrate for electrical contact may include commonly used methods such as welding, taping, clamping, stapling, riveting or other mechanical means. Because the metal of the metallized substrate can be very thin to achieve an interface that allows high current flow, face-to-face contact is usually required to provide a high surface area between the means for electrical contact through the housing and the metallized substrate. In order to carry sufficient current, this surface area should be greater than 1 square millimeter (10 -12 square meters), but may need to be greater than 3 square millimeters, even 5 square millimeters or more preferably 10 square millimeters.

[0084] The liquid electrolyte is typically a combination / mixture of a polar solvent and a lithium salt. As described above, commonly used polar solvents include propylene carbonate, ethylene carbonate, dimethyl carbonate, and diethyl carbonate, etc., but other polar solvents including ionic liquids and even water may also be used. Commonly used lithium salts in the industry include, but are not limited to, LiPF6, LiPF4, LiBF4, LiClO4, etc. The electrolyte may also contain additives known in the art. In many cases, the electrolyte may be flammable, wherein the safety characteristics of the metallized substrate current collector of the present invention may be beneficial in preventing dangerous thermal runaway events that result in fires and damage to the battery and the exterior of the battery.

[0085] Although embodiments of batteries with metallized thin film current collectors having low internal resistance have been described in detail, it is apparent that modifications and variations may be made thereto, all of which fall within the true spirit and scope of the present invention. With respect to the above description, it should be recognized that the optimal dimensional relationships of the technical parts of the present invention, including variations in size, material, shape, form, function and mode of operation, assembly and use, are obvious to those skilled in the art, and all equivalent relationships illustrated in the drawings and described in the specification are intended to be covered by the present invention.

[0086] The following description and examples are merely representative of potential embodiments of the present invention. One of ordinary skill in the art will well appreciate the scope of this disclosure and its breadth in terms of the following claims.

[0087] As described above, the present invention is a major shift and is contrary to all previous understandings and remedies performed within the lithium battery (and other energy storage device) industry. On the contrary, the novel devices described herein provide many beneficial results and characteristics that have not been explored (let alone unexpected) in this area to date. Initially, although as a comparison, it is important to note the obvious differences involved between existing devices and the devices currently disclosed and broadly covered by the present invention.

[0088] This counterintuitive example and the resulting consequences are associated with a heretofore unexplored, significant change in the application and use of a unique coupling of electrode materials with metallized thin film current collectors within electrochemical cells (rechargeable batteries, capacitors, etc.). This novel example includes at least five different alternatives, as detailed below.

[0089] Option 1 - Thin electrode coating

[0090] Electrodes are typically produced by applying electrode material to a current collector. Typically, very high power cells can be made by taking a thick metal foil and applying a thin electrode coating on it, thereby reducing the internal resistance of the cell to the point where power can be introduced and removed very quickly.

[0091] However, in contrast, the standard practice is to use a metallized thin film current collector and apply it with an extremely thin coating of electrode material, as disclosed herein. As discussed in the present invention, this counterintuitive method and practice leads to an unexpectedly effective reduction in the internal resistance of the target battery, especially compared to the results typically obtained using thick metal current collectors. This is contrary to current practice, where thick coatings are combined with thin metal plates to form high energy density batteries, while thin coatings are applied to thick metal plates to form high power batteries. Therefore, the combination of ultra-thin current collector metal coatings and thin electrode materials is also contrary to current technology and leads to unexpectedly safe batteries with low internal resistance for very high power potentials. In addition, according to the most advanced standard practice, thicker coatings are used to reduce the surface area of ​​the target current collector, thereby reducing the total weight of the battery in the form of kWh energy storage. Also contrary to intuition, it was unexpectedly found that when using a current collector with greatly reduced weight compared to a foil current collector, the electrode coating thickness can also be significantly reduced, thereby resulting in the above-mentioned reduction in battery internal resistance without increasing the total weight per kWh of the target battery. Such results, and the low resistance levels achieved through the application of thin electrode coatings to ultra-thin current collectors, without intending to be bound by any particular scientific theory, are clearly related to the ability of ions and electrons to quickly pass through the thin electrode (conductive) coating, thereby reducing their resistance to the high power results levels required for the target battery itself.

[0092] To achieve such results, the resistivity of the metallized film (thin) current collector must be greater than 0.005 ohm / square (preferably greater than 0.01 ohm / square, more preferably greater than 0.015 ohm / square, most preferably greater than 0.025 ohm / square, up to about 0.5 ohm / square). Therefore, the current collector resistivity is also a feature of the target electrochemical cell in which such a current collector is present, because a low measurement is a starting point before any further adjustments and modifications to the electrode coating application.

[0093] The application of electrode coatings is an alternative method for reducing the battery resistance of the present invention in terms of electrode area energy density (less than 4 mAh / cm 2 , preferably less than 3.5, more preferably less than 3, still more preferably less than 2.5, even more preferably less than 2, further more preferably less than 1.5, most preferably less than 1), electrode coating thickness (preferably less than 70 μm, more preferably less than 60 μm, more preferably less than 50 μm, even more preferably less than 40 μm, most preferably less than 30 μm), and / or electrode coating area density less than 150 g / m 2 , preferably less than 120g / m 2 , more preferably less than 100g / m 2 In other words, the use of electrode materials exhibiting such areal energy density, coating thickness, and / or coating area density provides the unexpected result of producing low battery internal resistance even in the presence of a highly resistive ultrathin current collector.

[0094] This combination of an ultrathin current collector and an ultrathin electrode coating provides an electrochemical device that exhibits a product of capacity CAP and resistance R, CAP×R less than at most 40 mOhm-Ah (preferably at most 35, more preferably at most 30, more preferably at most 25, and most preferably at most 20). Other ultrathin current collector electrochemical cell devices require a high resistance related to the battery capacity. However, contrary to this previous teaching, the use of an ultrathin electrode coating provides an overall low resistance even in the presence of a high resistance ultrathin current collector. Therefore, the thin electrode coating on the disclosed ultrathin current collector further obtains an electrochemical device having a total (overall) resistance measurement of less than 15 milliohms, preferably less than 12, more preferably less than 10, still more preferably less than 8, even more preferably less than 6, further more preferably less than 4, and most preferably less than 2. Likewise, as an alternative measurement of the capacity of such a high safety / low resistance electrochemical cell (or device), the capacity measured at 2C (30 minute discharge)>P×0.5C capacity (measured at 2 hour discharge) (where P is at least 90%, preferably at least 85%, more preferably at least 80%, more preferably at least 75%, most preferably at least 70%). Likewise, another measurement for such a novel high safety / low resistance (high power) electrochemical device is where the 4C (15 minute discharge) capacity>P×0.5C capacity, where P is a measurement value as described above.

[0095] Of greater interest is the ability of lithium-ion batteries to utilize ultrathin current collectors for safety purposes; however, as described above, such structures suffer from high internal resistance and subsequent high voltage drop at high currents. As described above, the use of low coating thickness electrodes unexpectedly and again effectively compensates for this disadvantage. For the capacity C of a lithium-ion battery cell, the current can be measured as the C ratio (usually referred to as the ratio of the current used to the current required to exhaust the battery in 1 hour). High internal resistance batteries perform poorly at C-rates greater than 1C, and the capacity measured at 2C or 4C is significantly lower. Therefore, it is difficult to achieve high capacity at 2C or 4C for batteries made with very thin metal current collectors. However, in contrast, applying thin electrode coatings to ultrathin current collectors has a surprising opposite effect, allowing significantly improved and feasible high capacity measurements. To date, there has been no other way to achieve such results except to effectively provide reduced internal resistance through the methods and operations for such batteries disclosed herein.

[0096] This combination of measurements and physical properties with an ultra-thin current collector has not been achieved in the past. Thus, by applying such a thin electrode coating as described above to such an ultra-thin current collector, the safety aspects associated with such a current collector are retained, but the internal resistance of the target cell is unexpectedly and effectively reduced to achieve high power charging and discharging, as is required for end-use rechargeable electrochemical cells that are not available at least at present.

[0097] Figure 2 A prior art structure of a thick coating electrode 11 applied to an ultra-thin current collector 12 is shown. Again, such a structure would exhibit high resistivity inside an electrochemical cell (a lithium-ion cell, as a non-limiting example).

[0098] therefore Figure 3 The reduction in the thickness of the electrode coating 15 applied to the ultra-thin current collector 16 is shown. As described above, this counterintuitive operation (within the state and standards of rechargeable electrochemical cells) is achieved by applying an internal low resistance (such as Figure 4 ) to compensate for the high resistance shown by the ultrathin current collector.

[0099] therefore Figure 4 Such an ultra-thin aluminized film current collector 21 is shown to be included in a battery cell 20. Applied to the collector 21 are shown thin positive electrode coatings 22, first separators 23, and relatively thin negative electrode coatings 24. Also present are second ultra-thin copperized film current collectors 21a and second separators 23a. Connected to the aluminized film current collectors 21 are internal tabs 25 for contacting external contacts (not shown) for charge transfer. As described throughout, such a battery 20 exhibits a level of safety associated with the presence of ultra-thin current collectors and high power capabilities associated with the counterintuitive use and application of thin electrode coatings on the surfaces of such current collectors.

[0100] The measurements, concerns and demonstrations of the metallized thin film current collector of the above-mentioned alternative 1 should also be understood to be the same as the other alternatives provided below. Therefore, in terms of structure and physical properties, the current collector described herein should at least be considered to be the same for all such alternatives (specifically avoiding repeating the same paragraphs above).

[0101] Option 2 - High Porosity Coating

[0102] It was also found that the ability to reduce the electrical path length required for ions and electrons to pass through the electrode coating by reducing the coating thickness can also be achieved by applying a high porosity electrode coating to such an ultra-thin current collector surface. In this way, without intending to rely specifically on any scientific theory, it seems that this low overall resistivity of the target battery is achieved by ions and electrons to regulate most of the travel distance through such an electrode coating through the porous structure, which is contrary to the typical low porosity type. This structural regulation also seems to allow more liquid electrolyte to penetrate deeper into the electrode, thereby apparently allowing electron transport through the positive electrode solid to be reduced, while still maintaining the high energy density associated with thicker coatings (even if the energy storage of the coating can be slightly reduced).

[0103] Typically, the porosity of lithium-ion electrode materials is desired to be low because high porosity increases the amount of electrolyte used and increases the volume used for a given amount of energy storage. Therefore, current typical battery practice uses batteries with calendared electrode coatings (under very high pressures) that exhibit high coating densities (or conversely low coating porosities). For the electrode coatings discussed above, typical high energy density batteries using ultrathin metallized current collector films include (particularly targeted) electrodes that exhibit high coating densities (low porosity). Therefore, for high porosity electrode coatings, thin electrode coatings as described above are counterintuitive according to current practice.

[0104] High porosity can be achieved, for example, by using a material with a relatively large particle size as an electrode coating. Such large particles form relatively large spaces between the particles, thereby increasing the porosity of the solid coating structure. Lower porosity layers can be achieved by using smaller particle sizes, which will achieve smaller interparticle spaces. Alternatively, a particle size distribution containing small particles will also achieve low density.

[0105] This highly porous structure can be measured based on the tap density of such electrode materials, and the porosity can be calculated based on such tap density measurements. True density is the theoretical density of a material, or the volume normalized theoretical density of a mixture. The tap density is obtained by mechanically tapping a graduated cylinder containing the sample until a small additional volume change is observed. Powder porosity is calculated by the following equation 1:

[0106] Powder porosity = 1 – tap density / true density Equation 1

[0107] The volume density of the coating is calculated as coating weight / m 2 Divide by volume / m 2 Therefore, the measurement / display is 20g / m 2 And the coating with a thickness of 20 microns has a 1.0g / cm 3 Therefore, the porosity of the coating was calculated by the following equation 2:

[0108] Coating porosity = 1 – bulk density / true density Equation 2

[0109] Applying this high porosity coated electrode to an ultra-thin current collector (as defined and described above for resistivity measurements), this increased (high) porosity coating provides the same low internal resistance routine measurements for the target electrochemical cell as the thin electrode coating alternatives described above.

[0110] Figure 5 A prior art structure of a low porosity coated electrode 31 applied to an ultra-thin current collector 32 is shown. Again, such a structure would exhibit high resistivity inside an electrochemical cell (as a non-limiting example, a lithium-ion cell).

[0111] therefore Figure 6 The reduction in electrode coating thickness 35 applied to an ultra-thin current collector 36 is shown. As described above, this counterintuitive operation (within the state and standards of rechargeable electrochemical cells) is achieved by applying an internal low resistance (e.g. Figure 7 ) to compensate for the high resistance shown by the ultrathin current collector.

[0112] therefore Figure 7Such an ultra-thin aluminized film current collector 41 is shown to be included in a battery cell 40. Applied to the current collector 41 is a high porosity positive electrode coating 44, a first separator 43, and a relatively high porosity negative electrode coating 42. Also present is a second ultra-thin copper film current collector 41a and a second separator 43a. Connected to the aluminized film current collector 41 is an internal tab 45 for contacting an external contact (not shown) for charge transfer. As described throughout, such a battery 40 exhibits a level of safety associated with the presence of an ultra-thin current collector and a high power capacity associated with the counterintuitive use and application of a thin electrode coating on the surface of such a current collector.

[0113] Option 3 - Highly Conductive Electrode Coating

[0114] Conductive additives such as carbon black or graphite are important components of lithium-ion batteries due to the limited conductivity of most electrode materials. However, since conductive additives do not store lithium themselves and therefore do not contribute to the energy storage capacity of the battery, their use is minimized in order to leave room for the maximum amount of lithium storage materials (such as NMC cathode materials). The coating of modern lithium-ion batteries contains only 3% conductive additives, with 3-5% being very common.

[0115] In general, the energy density maximization of typical and recent electrochemical cells combines the above-mentioned low porosity electrode coating with low conductivity carbon content. As described above, this structure maximizes the active conductive material (e.g., lithium ion structure) in the coating. The electrode coating with low porosity and low carbon content using ultra-thin current collectors (e.g., metallized films) will produce the same high resistivity battery results as described above. Although such high internal resistance can also lead to high safety levels (again, as described above), the lack of low resistance in the battery itself will damage its final use ability, thereby greatly limiting the power supply potential. However, the ability to increase carbon content (conductive material level) has not been realized in the rechargeable chemical battery industry. Therefore, according to this optional solution, it will be possible to achieve the ability of low-level internal resistance suitable for high volume power capabilities, ostensibly by increasing the carbon content in such electrode materials to adapt to faster conductivity. This counterintuitive operation and method allows the high resistance ultra-thin current collector structure to be combined with a low resistance electrode material, which is made by using more carbon in the coating and having a higher porosity.

[0116] Option 4 - Layered Electrode Coating

[0117] Another potential structural improvement of such electrochemical cells includes the use of multilayer electrodes with different gradients. Common electrode materials are made of single-layer electrode materials coated on current collectors. The optional scheme of the above-mentioned single thin electrode coating provides unexpectedly effective results of low internal resistance for the target battery, especially with a combination of high resistivity, safety level, ultra-thin current collectors (and coatings applied thereon). However, in charging and discharging, the electrode material portion away from the current collector will produce more resistance and ohmic heating than the electrode material portion very close to the current collector. Therefore, it is advantageous to make the material away from the current collector with a configuration having higher ionic and electronic conductivity than the material close to the current collector. Similarly, such a structure will produce lower resistance inside the target battery.

[0118] This structural and physical result can be achieved by a multilayer coating process, wherein the first coating applied (closest to the ultra-thin current collector surface) has a lower porosity and / or a lower conductive particle (carbon or graphite) content, and the porosity and / or conductive particle content increases with subsequent layers (preferably, the porosity and conductive particle concentration increase simultaneously with the subsequent layers). The increase in porosity can be achieved by reducing the pressure used during the calendering process of each successive layer. The content of conductive particles can be increased by increasing the proportion of conductive particles in the mixture.

[0119] like Figure 8 One configuration shown is that the first layer (Layer 1) 51B is closest to the substrate (current collector 52), is very thin and has high conductivity, followed by the second layer (Layer 2) 51A, which is a low porosity, low carbon content layer, and the third layer (Layer 3) 51, which has a higher conductive particle content and even high porosity. More layers can be applied in a similar manner, as described above, with each subsequent layer having a higher conductive particle content and higher porosity in a stepwise manner. In another configuration, the conductive "primer" layer is eliminated, and the lowest porosity, lowest conductive particle content layer is Layer 1, with each subsequent layer increasing in porosity and / or conductive particle content.

[0120] therefore Fig. 9 A multi-layer positive electrode coating 64 (composed of a thin aluminum film current collector 61) is shown applied to a battery cell 60. Figure 81, 2, 3; 51, 51A, 51B). Further provided is a first separator 63 and a relative multilayer negative electrode 64a (same structure as the positive electrode 64, but made of negative electrode materials, which is well known to ordinary technicians). Such a negative electrode is applied to a second ultra-thin copper film current collector 61a and a second separator 63a. Connected to the aluminum film current collector 61 is an internal tab 65 for contacting an external contact (not shown) for charge transfer. As described throughout, such a battery 60 exhibits a level of safety associated with the presence of an ultra-thin current collector and a high power capability associated with the counterintuitive utilization and application of a multilayer conductive gradient electrode coating on the surface of such a current collector.

[0121] Option 5 - Patterned Electrode Coating

[0122] Another method of achieving low internal resistance by changing the electrode material (which is different from the method generally used in the industry) involves using an electrode material having a specific pattern of conductive structures in contact with the surface of the target ultra-thin current collector. In this way, a first coating can be applied in discrete areas (whether linear rows, linear columns, diagonals, points, such as cubes, cylinders, or any other geometric three-dimensional shapes, etc.), and at least a second coating is applied in the area of ​​the target ultra-thin current collector surface to which the first coating has not yet been applied. The different coatings of this electrode material may include any of the above-mentioned structural limitations and requirements, including but not limited to a first coating exhibiting high porosity, a second coating exhibiting high conductivity, and any number of other coatings having different physical results in terms of conductivity, etc., providing a structure as required, as described above, to compensate for the high resistivity level imparted by the ultra-thin current collector itself. Therefore, with respect to the resistance measurement in these areas, different gradients may be produced using this patterned coating, allowing certain areas to drive ions and electrons faster than other areas.

[0123] So, in more detail, Fig.10 An ultra-thin current collector 73 is shown (again, providing a higher safety level for the target battery, but also accompanied by lower resistivity), to which a first coating 71 provided in three-dimensional lines has been applied and has one type of electrode configuration (e.g., high energy density made by using a lower conductive particle content, or lower porosity obtained by means such as smaller particle size materials), and a second coating 72, which is interspersed in three-dimensional alternating lines to the first coating 71, which has a different energy density and / or higher conductive particle concentration / content than the first coating 72. In this case, the higher porosity and / or higher conductive particle content area can act as a "highway" for ions and electrons, reducing the overall resistance inside the target battery, while maintaining a high energy density in the low porosity, low conductive particle content area according to a specific purpose (if necessary).

[0124] therefore Fig.11 The battery cell 80 is shown to include such an ultra-thin aluminum film current collector 81. The current collector 81 is shown to be patterned coated positive electrode 82, a first separator 83 and an opposite negative electrode coating 82a. The patterned positive electrode coating 82 includes the above (71 and 72) Fig.10 Such a negative electrode is applied to a second ultra-thin copper film current collector 84 and a second separator 83a. Connected to the aluminum film current collector 81 is an internal tab 85 for contacting an external contact (not shown) for charge transfer. As described throughout, such a battery 80 exhibits a level of safety associated with the presence of an ultra-thin current collector and a high power capability associated with the counterintuitive use and application of a patterned electrode coating on the surface of such a current collector.

[0125] Thus, the above examples have been demonstrated to show the ideal thickness, metal coating and conductivity results needed to prevent thermal runaway within electrolyte-containing cells, thereby providing not only a safer and more reliable type, but it also requires less internal weight components than ever before without sacrificing safety, but in fact improving performance. However, in addition, the ability to compensate for the high resistivity levels of such ultra-thin current collectors by applying different types of electrodes described herein that have not been disclosed or explored in the relevant electrochemical cell industry to date. The ability to pass such low resistance internally to the target cell through this unique combination of electrodes and ultra-thin current collectors, thereby allowing significant improvements in the following aspects, namely, not only in safety due to thermal runaway potentials within rechargeable and similar types of batteries and power batteries, but also in ensuring that high-power charging and discharging (as needed) for such electrochemical cells for certain end-use applications is not compromised.

[0126] After describing the present invention in detail, it will be apparent that those skilled in the art will be able to make changes and modifications to the present invention without departing from the scope of the present invention. Therefore, the scope of the present invention should be determined only by the appended claims.

[0127] Therefore, the above content is only regarded as an explanation of the principle of the present technology. In addition, since many modifications and changes will be easily made by those skilled in the art, it is not desired to limit the present technology to the exact construction and operation shown and described, so all suitable modifications and equivalent schemes can be attributed to fall within the technical scope of the present invention.

Claims

1. A lithium electrochemical energy generation and storage device, comprising a negative electrode, a positive electrode, at least one separator between the negative electrode and the positive electrode, an electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode; wherein: The current collector exhibits a resistivity greater than 0.015 ohms / square; wherein the electrochemical device exhibits a 2C capacity greater than 70% of the capacity measured at 0.5C, wherein the current collector further comprises an insulating support layer coated with at least one conductive layer, wherein the at least one conductive layer has a thickness less than 2 microns.

2. The lithium electrochemical energy generation and storage device according to claim 1, wherein: The device exhibited less than 4 mAh / cm 2 The energy density of the electrode area.

3. A lithium electrochemical energy generation and storage device, comprising a negative electrode, a positive electrode, at least one separator between the negative electrode and the positive electrode, an electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode; wherein: The current collector exhibits a resistivity greater than 0.005 ohms / square and a thickness no greater than 2 microns; wherein at least one of the negative electrode or the positive electrode is configured to achieve low resistivity by including at least one of: a. Electrodes with a thickness of less than 70 microns; b. an electrode coating containing greater than 6 wt % of a conductive additive; c. Electrode coating with porosity greater than 35%; d. having a multi-layer electrode coating; and e. An electrode coating exhibiting a dispersion pattern of a coating material, wherein at least one component of the dispersion pattern of the coating material comprises a region of high energy, lower conductivity, and at least one other component of the dispersion pattern of the coating material comprises a region of higher conductivity, wherein such conductivity is caused by the presence of a high conductive material content or a high porosity material.

4. An energy storage device, comprising: Negative and positive electrodes; a first separator interposed between the negative electrode and the positive electrode; Electrolytes; a first current collector in contact with at least one of the negative electrode and the positive electrode; a second current collector in contact with at least one of the negative electrode and the positive electrode, wherein at least one electrode of the second current collector is opposite to at least one electrode of the first current collector; and a second separator in contact with the negative electrode or the positive electrode; Wherein at least one of the first current collector and the second current collector exhibits a resistivity greater than 0.005 ohm / square. 5 . The energy storage device of claim 4 , further comprising a tab connected to the first current collector and configured to contact an external contact.

6. The energy storage device according to claim 4, wherein: The first current collector and the second current collector each include a metal film coated thereon.

7. The energy storage device according to claim 6, wherein: The metal film of the first current collector is a different metal from the metal film of the second current collector.

8. The energy storage device according to claim 7, wherein: The metal film of at least one of the first current collector and the second current collector has a coating thickness of less than 5 micrometers in total.

9. The energy storage device according to claim 4, wherein: The negative electrode and the positive electrode are porous, exhibiting a porosity of at least 35%.

10. The energy storage device according to claim 4, wherein: The negative electrode and the positive electrode both include an electrode coating, and the electrode coating contains more than 6 weight percent of a conductive additive.

11. The energy storage device according to claim 4, wherein: The negative electrode and the positive electrode each have multiple layers including a top layer having a higher conductivity than each successive lower layer.

12. The energy storage device according to claim 4, wherein: The negative electrode and the positive electrode each have multiple layers including a top layer having a higher porosity than each successive lower layer.

13. The energy storage device according to claim 4, wherein: The positive electrode is a patterned electrode, and a portion of the positive electrode includes a first region interspersed with a second region, wherein the first region has a first energy or a first conductivity property, and the second region has a second energy or a second conductivity property greater than the first region, thereby generating a conductivity gradient.

Citation Information

Patent Citations

  • Lithium energy storage device with internal fuse

    US10854868B2